The Wallace Collection catalogue of Italian sculpture - Kim, Seoyoung 1985- (The Trustees of the Wallace Collection, 2016)
The new catalogue of Italian sculpture in the Wallace Collection by Jeremy Warren, author of the award-winning catalogue of 'Medieval and Renaissance sculpture in the Ashmolean Museum, Oxford', puts onto the map a part of the Wallace Collection which has hitherto been relatively little-known. The 159 entries cover works in bronze, marble, terra cotta and wood dating from c. 1400 to 1900, and by or associated with some of the most famous names in Italian sculpture, such as Donatello, Pietro Torrigiani, Giovanni Bologna (Giambologna) and Alessandro Algardi. Each entry is packed with information, with a comprehensive description and bibliography followed by a commentary exploring attribution, dating, function and social and historical context. An introductory essay explores the origins of the Italian sculpture collection in the Wallace Collection, whilst in her technical essay Seoyoung Kim examines some of the results of the program of alloy analysis of the sculptures in bronze and other metals
Keywords: Wallace Collection (London, England) / Catalogs; Wallace Collection (London, England); Wallace Collection; Sculpture, Italian / England / London / Catalogs; Sculpture, Italian; Plastik; England / London; Italien; Katalog